2020
DOI: 10.1002/ajmg.a.61813
|View full text |Cite
|
Sign up to set email alerts
|

Screening of a large Rubinstein–Taybi cohort identified many novel variants and emphasizes the importance of the CREBBP histone acetyltransferase domain

Abstract: Pathogenic variants within the CREBBP and EP300 genes account for the majority of individuals with Rubinstein-Taybi syndrome (RSTS). Data are presented from a large cohort of 395 individuals referred for diagnostic testing of CREBBP, and of the 19 CREBBP missense variants classified as likely pathogenic in this study, 17 were within the histone acetyltransferase (HAT) domain, providing evidence that this domain is critical to the normal function of the CREBBP protein (CBP). The data presented here, combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
(61 reference statements)
1
11
1
Order By: Relevance
“…The syndrome has been subdivided into type 1 associated with the CREBBP mutation spectrum (RSTS1; OMIM #180849) and type 2 associated with the EP300 mutation spectrum (RSTS2; OMIM #613684). The frequency of abnormalities in the responsible CREBBP gene is approximately 55–75% of cases [ 2 , 12 , 13 , 37 , 65 , 94 , 95 , 96 , 97 , 98 , 99 ]. To date, 500 pathogenic variants in this gene have been referenced as causing RSTS1 (55 of which are unpublished) based on the HGMDPro variant and LOVD databases (analyzed on 27 April 2021) [ 100 , 101 ] ( Tables S1 and S3 ).…”
Section: Genotype and Mutation Spectrummentioning
confidence: 99%
See 3 more Smart Citations
“…The syndrome has been subdivided into type 1 associated with the CREBBP mutation spectrum (RSTS1; OMIM #180849) and type 2 associated with the EP300 mutation spectrum (RSTS2; OMIM #613684). The frequency of abnormalities in the responsible CREBBP gene is approximately 55–75% of cases [ 2 , 12 , 13 , 37 , 65 , 94 , 95 , 96 , 97 , 98 , 99 ]. To date, 500 pathogenic variants in this gene have been referenced as causing RSTS1 (55 of which are unpublished) based on the HGMDPro variant and LOVD databases (analyzed on 27 April 2021) [ 100 , 101 ] ( Tables S1 and S3 ).…”
Section: Genotype and Mutation Spectrummentioning
confidence: 99%
“…There are no real hot spot mutations in CREBBP with a mutational spectrum distributed along the 31 exons. However, some recurrent mutations have been described and it is noted that about 52% of the reported missense mutations are located in the lysine acetyltranferase (KAT domain) [ 99 ]. An exception to this is the presence of an unstable region of CREBBP located between introns 1 and 2, characterized by a high frequency of repeated or palindromic sequences resulting in recurrent rearrangements in this region [ 37 , 102 , 103 , 104 ].…”
Section: Genotype and Mutation Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…Second, it is expected that the diagnostic yield will be improved if WGS is used as the firstline approach for diagnosis, rather than a combination of exome sequencing and array-CGH analyses. Several studies analyzing divergent disease-causing variants in a large cohort recommended direct sequencing, multiplex ligation-dependent probe amplification, and array-CGH analyses of CREBBP and EP300 [23][24][25][26]. However, to the best of our knowledge, no previous study has identified deletions of the5 0 -UTR or deep intron-specific deletions of CREBBP.…”
mentioning
confidence: 99%